Roof Top Rain Water – Harvesting, Collection and Utilization - Ramanjaneyulu, A. V.; Sainath, N. (Chronicle of Bioresource Management, 2023)
Water is life and is essential for sustenance of all living organisms. Rapid increase in population, urbanization, industrialization and crop intensification, pollution and climate change can be attributed to increasing water shortage. Rainfall is the primary source for all water bodies on the earth like wells, ponds, lakes, rivers and recharging of underground aquifers. Of many rain water management strategies in rural and urban areas, harvesting rain water from roof tops and utilization for multiple purposes depending on the quality and demand and supply factors, is the need of the hour. However, meticulous planning and designing with all precautions are important for sustainable rain water management.